Magnetic resonance imaging-guided transurethral ultrasound ablation for benign prostatic hyperplasia: 12-month clinical outcomes of a phase I study - Viitala Antti; Anttinen Mikael; Wright Cameron; Virtanen Ilari; Mäkelä Pietari; Hovinen Topi; Sainio Teija; Saunavaara Jani; Taimen Pekka; Sequeiros Roberto Blanco; Boström Peter J (Wiley, 2022)
Objectives To investigate the safety and feasibility of magnetic resonance imaging (MRI)-guided transurethral ultrasound ablation (TULSA) for the treatment of benign prostatic obstruction (BPO).
Patients and methods An investigator-initiated, prospective, registered (NCT03350529), phase I study enrolled men with lower urinary tract symptoms due to benign prostatic hyperplasia in need of surgical intervention. Patients were followed for 12 months after TULSA. Uroflowmetry, prostate-specific antigen (PSA) level, and a comprehensive set of functional questionnaires including the Expanded Prostate cancer Index Composite-26, International Prostate Symptom Score (IPSS) and five-item version of the International Index of Erectile Function were obtained at baseline and every 3 months afterwards. MRI was obtained at baseline, and at 3 and 12 months after TULSA. Medication use before and after TULSA were recorded. Adverse events (AEs) were reported using the Clavien-Dindo classification.
Results A total of 10 men underwent TULSA with no severe AEs encountered. The baseline median (interquartile range [IQR]) age and prostate volume were 68 (63-72) years and 53 (45-66) mL, respectively. At baseline, six patients were moderately symptomatic and four patients severely symptomatic. Nine patients at baseline were on BPO medication. The median (IQR) improvement in the IPSS was 82%, from 17.5 (15.3-23.0) at baseline to 4.0 (2.3-6.3) at 12 months. Similarly, the median maximum urinary flow rate improved by 101%, from a median (IQR) of 12.4 (8.8-17.6) mL/s at baseline to 21.8 (17.6-26.5) mL/s at 12 months. Improvements were already seen at 3 months. The median prostate volume and PSA reduction at 12 months were 33% and 48%, respectively. There were no changes in continence, sexual, erectile or bowel functions. At 12 months, five out of six men with normal ejaculatory function before TULSA reported normal antegrade ejaculations. All patients taking BPO medication before TULSA discontinued medication after TULSA.
Conclusion TULSA appears to be a safe and effective treatment for BPO, with promising 12-month follow-up outcomes. Further studies with larger cohorts are needed to confirm the observed results.